Effectiveness of Soursop Leaf Extract (Annona muricata l.) on IL-6 Levels in Mammary Sprague dawley Female Rats Induced by Staphylococcus aureus - Purnamasari, Feby; Yulianty, Risfah; Latief, Syamsa (Unnes Journal of Public Health)
Research this aiming for analyze effectiveness extract leaf soursop could take effect to IL-6 levels at mammae rat female Sprague Dawley induced Staphylococcus aureus. Research this use type research Experiment Moot or quasi-experimental design with the design of the Post-test Only Control Group Design by looking at the 3th and 6th day IL-6 levels after induction bacteria Staphylococcus aureus and giving treatment on mammae rat female Sprague Dawley. Taking sample blood done at eye rat 2 times with examination elisa kit. Data analyzed with use Hock and Post test followed by the Mann Whitney test . Research results to show that not there is difference IL-6 levels at group control (?=0,062 > ? =0,05) and group antibiotics (?=0,0514 > ? =0,05). On group leaf soursop (?=0.037 < ? =0,05) and group antibiotics + leaves soursop and on group control (?=0.030 < ? =0,05) to show there is difference levels IL-6. Value mean on group soursop 7.50 ± 1.74 pg/ml day to3, and 7.50 ± 1.74 1 pg/ml day 6. Value mean on group soursop + antibiotics 7.46 ± 26t.66 pg/ml Day 3, and 4.73 ± 1.36 pg/ml day 6. The implication of this study is that soursop leaf extract or combination of antibiotic + soursop leaf extract can be as a complementary therapy for mastitis caused by the bacteria Staphylococcus aureus. Keywords: Extract Leaf Soursop, Levels IL-6, Rat Sprague Dawley Females